Proposed interior design of Nasi Lemak Antarabangsa Kampung Baru Restaurant for Shaha Corporation Sdn Bhd at Lot 1311N &1312N Jalan Raja Ekram, 30450 Bandar Ipoh, Perak Darul Ridzuan / Dali Mahat - Mahat, Dali (Faculty of Architecture, Planning and Surveying, 2011)
This report is the result of study and data collection to assist in the design of the proposed project at the end of restaurant. Students are required to prepare a comprehensive design scheme based on the research issues, the scope of client requirements and observations that are sensitive to particulars issues or problems that exist in the architectural design process restaurant. This project is to provide a new design for the restaurants in addition to creating a practical and new concepts to customers by providing quality services. The selection of this project is to highlight the new design for the restaurants is shaded by the natives. Development of restaurants in Malaysia is very exciting and profitable. Therefore, not suprising if we find the center of laundry now so many that grow like mushrooms after rain. It exists wherever the opportunity to see, like home stores, in shopping mall, in lots of shops, lots of office or at home. In general, restaurants can be classified based on the services provided and the target visitors. Nowadays, there are so many restaurants that serves different types of delicious food and cuisine all around the world. Most Malaysians love to eat food of different culture. This happens because Malaysia is a multi racial population with different culture. Each race and culture have different methods and ways of preparing their food. So there are more advantages in setting up an Malay restaurant so that it can add more variety to the food industry in Malaysia.